Optimization of Early Detection Management to Prevent the Spread of False Information to Realize a “Presisi” Police - Simangunsong, Daniel (Advances in Police Science Research Journal, 2024)
False information has been a real public order disturbance in Indonesia, without exception regency of Pati. Specially at this moment, there is a social media platform that make information spread very quick. Information that haven’t been true, could make a wrong perception and make it worst that can create divisions between society. Indonesian police through operational transformation with a predictive policy through out early detection based on data hopefully could be one of the solution to prevent false information. This research are meant to discover all of the causes that make enforcement intelligence unit of early detection in the jurisdiction of Pati Police has not been optimal. Methods that are used in this research are qualitative approach with analyze concept as the type of the research. Collecting data are held by doing observation, interview, and document studies. Data analysis techniques used include data collection, data reduction, data presentation, and drawing conclusions. The conceptual literature used includes management theory, SWOT analysis theory, patrol concept, theft concept, and optimization concept. The fatual condition in this reasearch is a spreading false information that happened in regency of Pati and an enforcement of early detection by intelligence unit of Pati Police. Optimization on controlling early detection is used in making planning administration that required, organizing through members in each unit, actuating through the right way, and also controlled and supervised by the leaders. Internal factors such as lack of quantity and quality of personel, lack of budget, less of facilities and infrastructure maintenance. On the other hand, the external factors are namely the lack of coordination and cooperation from the community or related functions in supporting early detection. The conclusions obtained from this study are that the implementation of early detction by the Intelligence unit of Pati Police in preventing false information spreading is still not opitmal and maximized. This is in the line with the optimization of early detection by Intelligence unit to prevent false information spreading are still concidered to have not produced optimal results.